Back Cover: Facile Construction of Quinoline‐2‐carboxylate Esters through Aerobic Oxidation of Alkyl 4‐Anilinocrotonates Induced by a Radical Cation Salt (Chem. Asian J. 14/2017). Issue 14 (3rd July 2017) - Jia, Xiaodong; Li, Pengfei; Shao, Yu; Yuan, Yu; Hou, Wentao; Liu, Xiaofei; Zhang, Xuewen; Ji, Honghe
Abstract : Making trees from the grass ! A facile construction of quinoline‐2‐carboxylate esters is described. In the presence of dioxygen and a radical cation salt, sp 3 C–H bonds in 4‐anilinocrotonates can be easily oxidized, and after a domino process, the pharmaceutically relevant quinoline derivatives were afforded in high yields, avoiding harsh reaction conditions and tedious starting material synthesis. More information can be found in the Communication by Xiaodong Jia et al. onpage 1719 in Issue 14, 2017 (DOI:10.1002/asia.201700560 ).